Review of the state of Mediterranean and Black Sea fishery resources - Lleonart J. (The Mediterranean fisheries sector. A reference publication for the VII meeting of Ministers of agriculture and fisheries of CIHEAM member countries (Zaragoza, Spain, 4 february 2008), 2008)
The status and trends of the Mediterranean and Black Sea main fisheries resources is reviewed. In the Black Sea the small pelagic resources have more importance than the demersal ones and their history is characterized by the rise and fall of the small pelagics, mainly anchovy, between 1980 and 1990. In the Mediterranean demersals dominate catches although small pelagics are also very important. During the last ten years, demersal resources catches have decreased by 20% while small pelagics as a whole do not show any particular trend, although the increase of round sardinella should be noted. According to recent assessments the most important demersal species: hake, red mullets and some valuable crustaceans appear to be overexploited. Bluefin tuna fishing and farming are nowadays the most conflicting activities in Mediterranean fisheries.
7. Meeting of Ministers of Agriculture and Fisheries of CIHEAM Member Countries, 2008/02/04, Zaragoza (Spain)